2016
DOI: 10.1177/0956462415608333
|View full text |Cite
|
Sign up to set email alerts
|

Cervical HPV infection in Romanian women infected with HIV during early childhood

Abstract: Human papillomavirus (HPV) is the most common cause of cervical cancer worldwide, and Romania has the highest rate of cervical cancer in Europe. Sixty-five young Romanian women infected with HIV during early childhood and 25 control subjects were evaluated for the presence of cervical HPV infection and for cytologic abnormalities. HPV infection was evaluated longitudinally in 42 HIV-infected individuals. Overall 28/65 (43.1%) of HIV-infected and 8/25 (32.0%) of uninfected subjects were infected with HPV, and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The scale of this difference emphasizes the greater vulnerability of Asian PHIV adolescents to longterm cancer risk. One-third of our adolescents had abnormal cervical cytology, which was consistent with an earlier US PHIV cohort (30%; mean age 19 years) [23] but higher than a parenterally infected Romanian cohort (25%; mean age 23 years) [24]. Furthermore, on colposcopy, condyloma acuminata and CIN 1 and CIN 3 on either visual inspection or biopsy were only detected among PHIV participants (42% vs 0% of those evaluated), raising concerns about the relative severity of disease they experience.…”
Section: Discussionsupporting
confidence: 88%
“…The scale of this difference emphasizes the greater vulnerability of Asian PHIV adolescents to longterm cancer risk. One-third of our adolescents had abnormal cervical cytology, which was consistent with an earlier US PHIV cohort (30%; mean age 19 years) [23] but higher than a parenterally infected Romanian cohort (25%; mean age 23 years) [24]. Furthermore, on colposcopy, condyloma acuminata and CIN 1 and CIN 3 on either visual inspection or biopsy were only detected among PHIV participants (42% vs 0% of those evaluated), raising concerns about the relative severity of disease they experience.…”
Section: Discussionsupporting
confidence: 88%
“…Half of 294 (50.6%) of the study participants said cervical cancer is preventable, which is substantially higher compared to findings in other settings. Much lower proportion was reported in Johannesburg, Burkina Faso, and LAO PDR [27][28][29]. These variations may in part reflect differences in awareness creation strategies, including the extent of media coverage, and as well as cultural differences.…”
Section: Discussionmentioning
confidence: 91%
“…Other studies have also shown that HIV-positive women have a higher frequency of multiple HPV infections and greater genotypic diversity, but have a tendency for greater distribution of oncogenic viral types, mainly 16, 18, 31, 33 and 45. [24][25][26] Similarly, Castilho and colleagues published hrHPV prevalence results of 65% in a cohort of 590 HIV-positive women by using hybrid capture-based genome testing. Besides, they also showed that 32% of the women studied had more than one type of high-risk HPV detected.…”
Section: Discussionmentioning
confidence: 99%